The Laparoscopic Surgical Skills programme: setting the European standard - Buzink, S. N. (2012)
This paper presents the overall outline of the Laparoscopic Sur- gical Skills programme (LSS) and the first level (LSS Grade 1 Level 1). In addition, preliminary results of the first LSS accred- ited courses are presented, of which one recently took place in Hospital Universitário de Santa Maria in Lisbon.